2011
DOI: 10.1542/peds.2010-1172
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events After the Use of Benznidazole in Infants and Children With Chagas Disease

Abstract: Treatment with benznidazole was well tolerated in children. Most ADRs were mild and did not require treatment suspension. A strong association was observed between ADR incidence and patient age, and most ADRs occurred in children older than 7 years. We believe that anxiety over potential severe ADRs in children with Chagas disease is not justified and should not be an obstacle to using benznidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 34 publications
8
108
1
3
Order By: Relevance
“…This result is in accordance with recent findings presented by Lobo et al (43), in which a greater incidence rate of ADRs was observed in adults than in children and older patients (61.0% versus 18.9% and 20.0%, respectively; P ϭ 0.0001) in a cohort of hospitalized patients at a tertiary care hospital in Northern Brazil. However, previous studies have shown a higher incidence of ADRs related to BZN in elderly patients (14), while a low incidence of ADRs was described for children and adolescents (44)(45)(46). As our study did not include individuals older than 65 years, this could explain the higher incidence of ADRs found by us among adults.…”
Section: Discussionmentioning
confidence: 58%
“…This result is in accordance with recent findings presented by Lobo et al (43), in which a greater incidence rate of ADRs was observed in adults than in children and older patients (61.0% versus 18.9% and 20.0%, respectively; P ϭ 0.0001) in a cohort of hospitalized patients at a tertiary care hospital in Northern Brazil. However, previous studies have shown a higher incidence of ADRs related to BZN in elderly patients (14), while a low incidence of ADRs was described for children and adolescents (44)(45)(46). As our study did not include individuals older than 65 years, this could explain the higher incidence of ADRs found by us among adults.…”
Section: Discussionmentioning
confidence: 58%
“…The prevalence of Chagas disease in pregnant women in Latin America ranges from 5% to 40% depending on the geographical area, and the rate of vertical transmission is esti- mated to be 4% to 10% (32). Due to the shortage of biomarkers specific for the acute stage (32,33), the current serologic tests are misleading in the early diagnosis of congenital T. cruzi infections, and a parasitological test should be performed on newborns for diagnosis (22). Within this framework, we evaluated the potential use of TSSA-CL in the serodiagnosis of congenital infections.…”
Section: Resultsmentioning
confidence: 99%
“…Serum samples were collected from infected and noninfected subjects. Clotted blood was obtained by venipuncture and analyzed for T. cruzi-specific antibodies by 2 commercially available kits, an ELISA using total parasite homogenate and IHA (both from the Wiener lab, Argentina) (22). Different panels of serum samples were used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…11 Nonetheless, when newborns are treated before 1 year of age, infection is cleared in almost all cases without the secondary effects common among adults. 11,13 Diagnosis in neonates is possible immediately after birth through parasitological methods, such as visualization of trypomastigotes on peripheral or cord blood, as well as blood concentration techniques (Strout or microhematocrit 14 ), whereas serologic diagnosis is possible starting at 8 months after birth, when potentially confounding maternal antibodies have disappeared. 11 Additionally, recent data suggest that parasitological treatment of young infected women may help prevent congenital transmission later in life.…”
mentioning
confidence: 99%